FEATURES AND DEVELOPMENT OF BUSINESS TOURISM - Aminov, Fazlitdin (THE INNOVATION ECONOMY, 2024)
The article emphasizes the fact that business tourism is an important service sector and an important source of income, as well as the presence in Uzbekistan of large untapped reserves, as well as new organizational, economic and management solutions for their successful use. Today, business tourism is an important service sector and an important source of income for countries around the world. Our country has large reserves that are expected to be used in this area, but their effective use requires the development of new, innovative organizational, economic and management mechanisms, modern marketing development programs that will allow us to generalize global and local experience, and sustainable economic development. Business tourism services and the tourism industry as a whole require the development of an effective strategy. As a result, it is appropriate to make necessary scientifically based suggestions and recommendations in this regard.